Premenstrual Syndrome and Its Impact on the Quality of Life of Female Medical Students at Bisha University, Saudi Arabia - Al-Shahrani AM; Miskeen E; Shroff F; Elnour S; Algahtani R; Youssry I; Ahmed S (Journal of Multidisciplinary Healthcare, 2021)
Abdullah M Al-Shahrani,1 Elhadi Miskeen,2 Farah Shroff,3 Suaad Elnour,2 Rawan Algahtani,4 Ilham Youssry,5 Samar Ahmed6 1Department of Family Medicine, College of Medicine, University of Bisha, Bisha, Saudi Arabia; 2Department of Obstetrics and Gynaecology, College of Medicine, University of Bisha, Bisha, Saudi Arabia; 3Department of Family Practice, School of Population and Public Health, Faculty of Medicine, University of British Columbia, Vancouver, BC, Canada; 4College of Medicine, University of Bisha, Bisha, Saudi Arabia; 5Department of Pediatrics, Cairo University, Cairo, Egypt; 6Forensic medicine and clinical toxicology department, Faculty of Medicine, Ain Shams University, Cairo, EgyptCorrespondence: Abdullah M Al-ShahraniDepartment of Family Medicine, College of Medicine, University of Bisha, P.O. Box 1290, Bisha, 61922, Saudi ArabiaTel +966504639678Email ab_alshahrani@ub.edu.saObjective: The severity and chronicity of PMS can lead to the impairment of studies, and it can also affect relationships, activities, quality of life (QoL), and academic performance. This study aimed to determine PMS frequency and its associated factors in order to assess the quality of life (QoL) among female medical students at Bisha University, Saudi Arabia.Methods: This study was cross-sectional and included 388 female medical students in the Faculty of Medical Applied Sciences and the Faculty of Medicine at Bisha University. The participants all filled in a self-administered questionnaire. The Premenstrual Syndrome Scale (PSS) was used based on the diagnostic and statistical criteria for PMS assessment. PMS was diagnosed after the presence of five or more severe premenstrual symptoms had been resolved following menstruation (adapted from American Psychiatric Association).Data Analysis: The data obtained were analyzed using SPSS 25.0. A chi-square test was used to test the associations between the study variables. A logistic regression analysis technique was used to select the group of variables. Participants were asked to provide consent to participate in the study. IRB was obtained from the University of Bisha, College of Medicine.Results: The participants were aged 19.5 ± 4.9 years, and the prevalence of PMS was 64.9%. Most of the female students were of extroverted personality types (35%). In addition, 13.4% were obese or overweight, and 19.5% of the 50% with PMS exercised regularly (p < 0.05). Menstruation significantly influenced the related quality of life subscales (p < 0.05).Conclusion: PMS significantly influenced daily activities related to quality of life and homework. Moreover, almost half of the female students experienced the effects of menstruation in their learning environment. Therefore, among female students, the modification of risk factors should be considered a critical intervention point.Keywords: PMS, medical students, quality of life, University of Bisha, Saudi Arabia